Analisis Potensi Sektor Pertanian Sebagai Pengembangan Sektor Unggulan di Kabupaten Probolinggo - Hafizh Risqullah Hadi Pratama; Nasikh Nasikh (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2022)
Porbolinggo Regency has potential in the agricultural sector, but its growth is unstable because it has not been managed optimally. The purpose of this research is to improve the economy through the agricultural sector by providing a discussion about the role of the agricultural sector in Probolinggo Regency as a sector that can be developed again so that the agricultural sector in Probolinggo Regency becomes a superior sector and is increasing in economic growth for prosperity. In this research using quantitative methods that use analytical tools such as Location Quotiens and Shift Share, using secondary data, namely Gross Regional Domestic Product (PDRB) of Probolinggo Regency and East Java Province in the period 2016-2020. The results of this study in the form of a picture of how the development and shift of the agricultural sector in Probolinggo Regency in the period 2016 to 2020 with a picture of these developments can certainly be insight in improving the agricultural sector in Probolinggo Regency.